Detecting hotspots of interactions between vegetation greenness and terrestrial water storage using satellite observations - Xie, Xiaoming; He, Bin; Guo, Lanlan; Miao, Chiyuan; Zhang, Yafeng (Remote sensing of environment, 2019)
Changes in water availability strongly affect vegetation growth, and vegetation can also modify land water storage by changing the land surface water balance. Here, based on the terrestrial water storage (TWS) data retrieved from the Gravity Recovery and Climate Experiment (GRACE)satellites mission and the normalized difference vegetation index (NDVI) from Jan. 2003 to Dec. 2015, we investigate the interplay between land water and vegetation greenness at a global scale. The results reveal a coherent trend with statistical significance between the terrestrial water storage anomaly (TWSA) and the NDVI in 20.90% of global vegetated lands in contrast to a non-coherent trend of 20.87% in global vegetated lands. Vegetation greenness exhibits a common 0- to 1-month delayed response to the TWSA, and significant positive TWSA-NDVI relationships appear in approximately 43.17% of global vegetated areas. A comparison study suggests that the response of vegetation greenness to the TWSA is more rapid than that to precipitation. Interactions between the TWSA and NDVI are further investigated by using the Granger causality test technique. Globally, a strong interaction between the TWSA and NDVI occurs in over 16.75% of vegetated areas. Simultaneously, vegetation greenness is found to be the Granger cause of the TWSA in over 40.34% of global vegetated areas, indicating widespread impacts of vegetation change on variations in land water storage. A case study in China suggests that vegetation greenness increase is an important reason for the decrease in the TWSA in North and Northwest China, which are traditionally water-limited-growth regions. In two humid regions, Southwest and South China, the influence of the TWSA on vegetation greenness seems to be stronger than that of vegetation greenness on the TWSA. Our study suggests that the GRACE TWS is a useful tool for investigations of interactions between vegetation greenness and land water conditions. •Temporal relationships between the NDVI and TWSA derived from GRACE were examined.•A significant response of the NDVI to TWSA was found over 43.17% of global vegetated areas.•The response of the NDVI to TWSA is more rapid than that to precipitation.•Interactions between the NDVI and TWSA were detected over 16.75% of global vegetated areas.